BLT1 signaling in epithelial cells mediates allergic sensitization via promotion of IL‐33 production. Issue 3 (9th December 2018) - Xiong, Yingluo; Cui, Xinyi; Li, Wenjing; Lv, Jiaoyan; Du, Lixia; Mi, Wenli; Li, Huabin; Chen, Zhengrong; Leng, Qibin; Zhou, Hong; He, Rui
Abstract: Background: Epithelial cells (ECs) play a crucial role in allergic sensitization to inhaled protease allergens by instructing type 2 innate lymphoid cells (ILC2) and dendritic cells (DCs) via release of pro‐type 2 cytokines, particularly interleukin‐33 (IL‐33). Leukotriene B4 (LTB4) is a well‐known leukocyte chemoattractant via engagement of its receptor 1 (BLT1). However, the role of LTB4‐BLT1 axis in allergic sensitization via activation of ECs is still unknown. Methods: We evaluated the effect of LTB4‐BLT1 axis on IL‐33 expression and ILC2 activation in vivo and in vitro. Chimeric mice were established to evaluate the contribution of BLT1 expression in nonimmune cell to allergic sensitization. Results: Genetical or pharmacological interruption of LTB4‐BLT1 axis during sensitization phase markedly reduced papain‐induced IL‐33 expression, decreased ILC2 activation and DC migration, thereby impairing the priming of allergic Th2 responses. Furthermore, papain inhalation induced a rapid release of LTB4 preceding IL‐33, and intranasal administration of LTB4 to naïve WT mice significantly increased IL‐33 expression and ILC2 activation in lung, which was absent in Il33 −/− or Ltb4r1 −/− mice. Furthermore, BLT1 was expressed in primary mouse ECs or normal human bronchial ECs (NHBE), and papain induced LTB4 release by NHBE, which in turn amplified IL‐33 production dependent on Akt activation via BLT1. Consequently, bone marrow chimeric mice lacking BLT1 in radio‐resistant structural cells failed to develop allergic lung inflammation to papain. Conclusion: Our study reveals a functional role of LTB4‐BLT1 axis in nonimmune cells, most likely lung ECs, in controlling allergic sensitization as an upstream regulator of IL‐33. Abstract : LTB4 is released rapidly upon allergen exposure and amplifies lung epithelial cell‐derived IL‐33 production and subsequent ILC2 activation. LTB4 directly up‐regulates IL‐33 production by lung epithelial cells via its receptor BLT1, which is dependent on Akt activation. BLT1 blockade or lack of BLT1 expression in radio‐resistant structural cells is required for activation of IL‐33‐ILC2 axis and the priming of allergic Th2 response to inhaled papain.